2017
DOI: 10.1016/j.bbagen.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of human adipose-derived stem cells using 810 nm and 980 nm lasers operates via different mechanisms of action

Abstract: Photobiomodulation (PBM) using red or near-infrared (NIR) light has been used to stimulate the proliferation and differentiation of adipose-derived stem cells. The use of NIR wavelengths such as 810nm is reasonably well accepted to stimulate mitochondrial activity and ATP production via absorption of photons by cytochrome c oxidase. However, the mechanism of action of 980nm is less well understood. Here we study the effects of both wavelengths (810 nm and 980 nm) on adipose-derived stem cells in vitro. Both wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 46 publications
2
100
0
Order By: Relevance
“…Recently Wang et al showed [108] that two different NIR wavelengths affected adipose-derived stem cells by distinctly different mechanisms of action. 810-nm laser was proposed to activate CCO leading to ATP production and a brief burst of ROS, but had no effect on intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Wang et al showed [108] that two different NIR wavelengths affected adipose-derived stem cells by distinctly different mechanisms of action. 810-nm laser was proposed to activate CCO leading to ATP production and a brief burst of ROS, but had no effect on intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…[107]. Furthermore, a recent study also indicates that the proliferation and differentiation of adipose-derived stem cells are regulated by 980nm IR radiation that is proposed to affect temperature-gated calcium ion channels, while 810nm IR radiation stimulated ATP production via absorption of photons by CCO [108]. …”
Section: Emerging Studies Of Infrared Therapymentioning
confidence: 99%
“…The most important alternative chromophore appears to be transient receptor potential (TRP) ion channels that can be activated by light or heat . An example is TRPV1 that can be activated by blue or green light and by longer wavelength NIR light (980 nm) that targets water in the form of nanostructured exclusion zone water clusters . Regardless of whether CCO is activated by red/NIR light, or TRP ion channels are activated by blue/green/980 nm light, the cellular results have some aspects in common, but also display some differences.…”
Section: Introductionmentioning
confidence: 99%
“…For example, citing the work of De Taboada et al (2011), Tsai and Hamblin specifically noted how pulsed doses of coherent 808 nm NIR laser light three times per week significantly reduced the numbers of amyloid-β plaque proteins in the brain, as well as the levels of this peptide in plasma and cerebrospinal fluid in a mouse model. While still citing this and another study (Wang et al 2016), another wavelength, namely 810 nm NIR, was also found to induce ATP generation which is said to enhance neuronal preservation and inhibit amyloid plaque formation (Tsai and Hamblin 2017, page 203). When it came to CCO, the second study found that CCO better absorbed 810 nm light than 980 nm light by a factor of 10-100 times, a finding attributed to several of CCO's underlying light-absorbing chromophore molecules with two copper centers Cu A and Cu B , and two heme (iron) centers.…”
Section: Introductionmentioning
confidence: 99%